Electromagnetic Step Signal Propagation in Lossy Waveguide - Yemelyanov, K. M.; Nikitskiy, S. B.; Tretyakov, O. A. (Видавничий дім «Академперіодика», 2013)
Electromagnetic Step Signal Propagation in Lossy Waveguide